The Effect of Person-Job and Person-Supervisor Fit on Job Satisfaction - Zheng, Fusheng; SangWoo Hahm, Xiu Jin, (Opción, 2019)
This study explores the role of self-efficacy and outcome expectancy as a concept related to expectations in the process of improving job satisfaction. In this study, we conducted a survey to employees of social enterprises in Korea and finally conducted an empirical analysis using 233 subjects as a method. As a result, Job fitness increases self-efficacy by making workers confident when doing their job well. In conclusion, Person-Job fit and Person-Supervisor fit influences motivation and then improves performance-related variables such as Job Satisfaction.